The Effect of Project Based Learning with Ethnoscience Approach on Science Conceptual Understanding - Sekar Dwi Ardianti; Sulasfiana Alfi Raida (Journal of Innovation in Educational and Cultural Research, 2022)
The purpose of this study was to analyze the effect of implementing a project-based learning model (PjBL) with an ethnoscience approach on the level of understanding of elementary school students' concepts and to determine student responses to the application of a Project Based Learning Model (PjBL) with an ethnoscience approach. This study was a quasi experimental research design with a post-test only group design. The samples used were two classes of fourth grade students as the Â experimental class consisted of 27 students and the control class consisted of 23 students. The sampling technique used was multiple purposive sampling. The data collection method used was the test and non test method. The instruments used are multiple choice post-test questions and student response questionnaires to the application of a project-based learning model (PjBL) with an ethnoscience approach.Â The normality and homogeneity test as the initial test showed the data were normally distributed and homogeneous. This study used the average difference test with the parametric statistical test Independent-Sample T Test. The t-test results showed that the t-count value is 2.452 t-table 2.011 so that there is a significant difference in the post-test mean of students in the experimental class and the control class. The average score of student responses to the use of the Project Based Learning Model (PjBL) model with an ethnoscience approach is 89.6 with very good criteria. The application of the Project Based Learning (PjBL) model with the ethnoscience approach affects science conceptual understanding.